Anti-Candida and anti-Cryptococcus evaluation of 15 non-alkaloidal compounds from Pterogyne nitens - Lima, Caroline Sprengel [UNESP]; Polaquini, Carlos Roberto [UNESP]; Santos, Mariana Bastos dos [UNESP]; Gullo, Fernanda Patrícia [UNESP]; Leite, Fernanda Sangalli [UNESP]; Scorzoni, Liliane [UNESP]; Bolzani, Vanderlan da Silva [UNESP]; Mendes-Giannini, Maria José Soares [UNESP]; Fusco-Almeida, Ana Marisa [UNESP]; Rezende, Andréia Alves [UNESP]; Regasini, Luis Octavio [UNESP] (Wolters Kluwer, 2016)
Objective To evaluate anti-Candida and anti-Cryptococcus activities of 15 non-alkaloidal compounds from Pterogyne nitens Tulasne (Leguminosae), a South American medicinal plant. Methods Compounds were submitted to antifungal assays, using microdilution method described by Clinical and Laboratory Standards Institute document, with minor modifications. Five species of Candida and two species of Cryptococcus, including clinical isolates were screened. Antifungal activity was expressed by minimum inhibitory concentration (MIC). Amphotericin B and fluconazole were used as standard antifungal drugs. Results Among tested compounds, six substances presented fungal growth inhibition (MIC < 31.2 μg/mL) [three flavone derivatives (1–3), a glycosylated flavonol derivative (5) and two phenolic acids (10 and 12)]. Sorbifolin (1), exhibited potent antifungal activity, demonstrating MIC value of 3.90 μg/mL against Candida glabrata ATCC 90030, Cryptococcus gattii 118 and fluconazole-resistant clinical isolate of Cryptococcus neoformans var. grubii. Pedalin (2) and nitensoside B (3), two glycosylated flavone derivatives, were active against Cryptococcus neoformans ATCC 90012 (MIC = 7.80 μg/mL). Conclusions Flavone derivatives from Pterogyne nitens can serve as prototypes for the design and development of innovative anti-Candida and anti-Cryptococcus hits.
Keywords: Antifungal; Candida; Cryptococcus; Flavonoid; Opportunistic fungi; Pterogyne nitens